Polypharmacy and Therapeutic Inertia in Extreme Longevity: A Potential Clinical Ageism Scenario Secondary to Important Gaps in Clinical Evidence - María Viviana Pantoja; Ivan David Lozada-Martinez (Korean Society for Preventive Medicine, 2024)
Population aging is a global health priority due to the dramatic increase in the proportion of older persons worldwide. It is also expected that both global life expectancy and disability-free life expectancy will increase, leading to a significant rise in the proportion of individuals with extreme longevity, such as non-agenarians and centenarians. The inaccuracy of clinical evidence on therapeutic interventions for this demographic could lead to biased decision-making, influenced by age-related beliefs or misperceptions about their therapeutic needs. This represents a potential clinical ageism scenario stemming from gaps in clinical evidence. Such biases can result in 2 significant issues that adversely affect the health status and prognosis of older persons: polypharmacy and therapeutic inertia. To date, documents on polypharmacy in non-agenarians and centenarians account for less than 0.35% of the overall available evidence on polypharmacy. Furthermore, evidence regarding therapeutic inertia is non-existent. The purpose of this letter is to discuss polypharmacy and therapeutic inertia as potential clinical ageism scenarios resulting from the clinical evidence gaps in extreme longevity.